Rancang Bangun Sistem Informasi Pencarian Data Objek Pemajuan Kebudayaan Kota Bengkulu dengan Algoritma Sequential Searching - Dyah Pujiastuti, Nur Rochmah; Ramadhandi, Wahyu Dwi (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2023)
Information media supports knowledge about cultural objects, especially Bengkulu. The search for cultural objects in Bengkulu City. with the desired keywords using the Sequential Searching Algorithm is a solution to the search problem. This study uses a system development that applies the Waterfall method. Methods that are serial namely Analysis, Design, Implementation, and Testing. System testing uses the System Usability Scale (SUS) to test user convenience and Blackbox Testing to test functionality. A web-based search information system for cultural promotion objects of Bengkulu City has been built by applying the Sequential Searching Algorithm. The SUS test with 30 respondents got a score of 83.75, according to the Acceptable Range scale, which is Acceptable, the Grade Scale scale, which is B, and the Adjective Rating scale, which is good. Black Box testing is carried out for 22 activities to get 100% results meaning the system is running well. Based on the results of keyword testing and search time, it has a real time average of 0.055 ms for the 10 data tested. It was concluded that the information system for the promotion of culture in the city of Bengkulu is feasible to use.